MONITORING OF HYDROCHEMICAL PROFILE OF LOWER STRETCHES OF RIVER DAMODAR, INDIA - PANIGRAHI, A. K.; PATTNAIK, SUBASINI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2019)
River Damodar is an important tributary of the Ganges. The key objectives of the present study were to determine the seasonal variations in the physicochemical characteristics of the riverine water at pre-designated stations and to evaluate the impact of pollution load on spatial and seasonal differences. Monthly investigation was carried out from March, 2017- February, 2018 to assess the water quality of the lower stretches of River Damodar. Ten Physicochemical parameters such as water temperature (T), pH, Electrical conductivity (EC), dissolved oxygen (DO), biochemical oxygen demand (BOD), total Dissolved solids (TDS),Nitrate, Phosphate etc. were monitored in four sampling stations of diverse eco-hydrological characteristics. The obtained dataset were treated using ANOVA and multivariate statistical techniques such as correlation matrix, Principal Component Analysis to assess the spatiotemporal variation and to identify most important factors governing the water quality of the river. The pH was found neutral to mildly alkaline (6.97-8.3) throughout the study period, while conductance was obtained in the range of 228.65 - 692.33μS/cm. The results of different parameters of Damodar river water are varied and Temperature (F=89.79, P<0.05) and nitrate level (F=10.87, P<0.05) displayed significant seasonal variation.DO (F=5.46, P<0.05), BOD (F=5.98, P<0.05) and TDS (F=6.67, P<0.05) significantly differed among sampling stations. The mean concentration of different water quality variables ranged as, DO- 4.76 to 7.53 mgLˉ1,TDS-86.0 to 648 mgLˉ1, PO43- 0.28to 1.17 mgLˉ1 , NO3–-0.43 to 3.21 mgLˉ1, SO42--10 to 57.19 mgLˉ1and BOD-0.96 to 5.57 mgLˉ1 respectively. Impact of the southwest monsoon and spatial heterogeneity were pronounced in the distribution of the TDS and inorganic nutrients. Results of Principal Component Analysis show that 4 varifactors/ PCs are accountable for 81.8% variation. This study would be helpful in formulating control strategy in near future.